Development of an Adaptive Curriculum Based on Outcome-Based Education (OBE) in the Information Technology Study Program at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Izhari, Fahmi (LENTERNAL: Learning and Teaching Journal, 2025)
This study developed an adaptive curriculum based on Outcome-Based Education (OBE) for the Information Technology Study Program at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The curriculum redesign aimed to directly align Course Learning Outcomes (CPMK) with Graduate Learning Outcomes (CPL), structured progressively across semesters to support competency formation through conceptual understanding, laboratory practice, and project-based assignments. Internal document analysis and academic discussions revealed gaps in vertical and horizontal alignment among learning outcomes, particularly in core areas such as programming, systems analysis, and digital business. The revised curriculum integrates project-based learning into at least 60% of core courses and embeds Islamic ethical values and local contexts into the learning design. Validation conducted by internal faculty teams confirmed that the curriculum is feasible and that the course mapping is relevant. The results indicate that a transparent and reflective internal process supported by institutional documentation can produce a curriculum that is responsive to the digital transformation era, even without involving external experts or alumni surveys. These findings provide practical implications for curriculum policy in Islamic higher education institutions and open opportunities for further research to assess the long-term impact of OBE implementation on graduate outcomes